2020
DOI: 10.1111/php.13332
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sublethal Blue Light on Herbal Extract Activity Against Volatile Sulfide Compound Production by Fusobacterium nucleatum

Abstract: Previously, we have shown that sublethal exposure of blue light caused increased cell membrane permeability in Fusobacterium nucleatum. The aim of the present study was to test the effect of this exposure on the activity of Lavender, Sage, Echinacea and Mastic gum extracts against volatile sulfide compound (VSC) production by Fusobacterium nucleatum. Bacterial suspensions were pre‐exposed to blue light (400–500 nm) bellow minimal inhibitory dosage (sub‐MID). Exposed and nonexposed samples were inoculated into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Previously, we have shown that exposing bacterial cells to a sub-lethal dosage of blue light increases their cell membrane permeability [9,11], and this suggested that this effect may increase the efficacy of antibacterial agents. In this study, we examined the combined effect of sub-lethal blue light and sodium fluoride on the cariogenicity of Streptococcus mutans in a biofilm configuration.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Previously, we have shown that exposing bacterial cells to a sub-lethal dosage of blue light increases their cell membrane permeability [9,11], and this suggested that this effect may increase the efficacy of antibacterial agents. In this study, we examined the combined effect of sub-lethal blue light and sodium fluoride on the cariogenicity of Streptococcus mutans in a biofilm configuration.…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies have suggested that the use of sub-lethal blue light may increase bacterial membrane permeability by inducing membrane damage, thus allowing antibacterial agents to enter the cell more easily and increase their effect [8,9]. Therefore, the aim of the present study was to test the premise that exposing Streptococcus mutans biofilm to blue light might induce membrane damage and increase the efficacy of fluoride to impair its abilities to produce and endure lactic acid.…”
Section: Introductionmentioning
confidence: 96%
“…Previous studies showed that sub-lethal dosage of blue light can increase cell membrane permeability in Fusobacterium nucleatum [13,14] and suggested that this effect was mediated through the production of reactive oxygen species [11]. In the present study, we tested the combined effect of sub-lethal blue light and silver nanoparticles on the ability of Fusobacterium nucleatum to produce malodor, its cell membrane integrity, and measured the levels of ROS produced following this treatment in order to understand the mechanism for the combined phototoxic effect.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies have demonstrated the phototoxic effect of blue light against malodor producing bacteria [10] with or without the added effect of photosensitizers [11] or photoactivators [12]. Furthermore, the main antibacterial mechanism of blue light against Fusobacterium nucleatum was shown to be membrane damage [13] that could be leveraged to increase the efficacy of other antibacterial agents [14]. The aim of the present study was to test the added effect of silver nanoparticles on blue light phototoxicity against Fusobacterium nucleatum.…”
Section: Introductionmentioning
confidence: 90%
“…All of the strains were cultured overnight (O/N) for 16 h. Following this, each O/N cell culture was diluted 1/100, and additional incubation was performed to ensure that all of the experiments were conducted in the mid-exponential phase (OD 600 of approximately 0.5). Blue light treatments were performed using a custom LED lamp that emitted light at an intensity of 0 to 80 W/m 2 , with the emission peaks ranging from 400 to 470 nm and centered at 462 nm ( 14 , 51 , 52 ). The wavelength was determined using a BLACK-Comet-SR Spectrometer (StellarNet, USA) with SpectraWiz Spectroscopy software (StellarNet) and SpectraWiz LabVIEW Software (StellarNet).…”
Section: Methodsmentioning
confidence: 99%